1989
DOI: 10.1007/bf01091900
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition and protein quality of minor millets

Abstract: Nutrient composition of five minor millets produced and consumed in dry land regions and tribal areas of Andhra Pradesh, India, was evaluated. The millets analysed were Italian millet (Setaria Italica), French millet (Panicum miliaceum), Barnyard millet (Echinachloa colona), Kodo millet (Paspalum scrobiculatum) and little millet (Panicum miliare). The nutrients analysed were proximate principles, amino acids, fibre components, calcium, Phosphorus and Iron. Protein and energy were evaluated by true digestabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 8 publications
1
38
0
2
Order By: Relevance
“…It has been reported that the expansion ratio of extruded cereals depends on the degree of starch gelatinization (Case et al 1992;Chinnaswamy and Hanna 1988). Kodo has starch content 79 % (Geervani and Eggum 1989), and a high gelatinization temperature of 82°C, as the temperature in this study ranges from 80-150°C, the ER is high. Moreover, chickpea also has a high (40-50 %) starch content (Huang et al 2007), which may favour an extrusion process to produce extrudates with good ER.…”
Section: Expansion Ratio (Er)mentioning
confidence: 63%
See 1 more Smart Citation
“…It has been reported that the expansion ratio of extruded cereals depends on the degree of starch gelatinization (Case et al 1992;Chinnaswamy and Hanna 1988). Kodo has starch content 79 % (Geervani and Eggum 1989), and a high gelatinization temperature of 82°C, as the temperature in this study ranges from 80-150°C, the ER is high. Moreover, chickpea also has a high (40-50 %) starch content (Huang et al 2007), which may favour an extrusion process to produce extrudates with good ER.…”
Section: Expansion Ratio (Er)mentioning
confidence: 63%
“…Nutrient composition of kodo is comparable to other major cereals having 65-72 % carbohydrate, 8-9 % protein, 1-2 % fat, 2-3 % minerals, and 9 % fiber. Starch content (79 %) favours extrusion process in developing directly expanded snack (Geervani and Eggum 1989). Also, gelatinization temperature of kodo is 77-90°C (Shinoj et al 2006) which is comparable to that of major cereals, which are generally used for extruded snack development.…”
Section: Introductionmentioning
confidence: 99%
“…The new fashion to grow common millet is not only as an alternative crop, or bird food crop, but is also cultivated for its unique nutritional value which is superior to main cereals of wheat, rice, oats, etc. Panicum flour is gluten-free and more easily digestible because of it's high alkaline content which counteracts acids, and high protein (10-15%) content (Chang, 1968;Geervani & Eggum, 1989). Some new cultivars such as 'Earlybird', 'Sunrise' and 'Hunstman' and new types with waxy starch were registered recently (Baltensperger et al, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Proso millet is cultivated for its unique nutritional value, which is superior to that of the more common cereals, wheat, rice, and oats. Since it has a high alkaline content that counteracts acids, and a high protein content, it is also considered a health food (Chang, 1968;Geervani and Eggum, 1989).…”
mentioning
confidence: 99%